(untitled) (Journal of Education and Development, 2019)
Technology-Rich Classrooms (TRCs) have been increasingly constructed in K12 schools. Existing studies revealed that to what extent TRCs play a role in shaping teaching and learning depends on what teachers expect to do and what they do with TRCs. This study aimed at exploring the gap between teachers’ experiences of existing TRCs and their expectations of ideal TRCs. A total of 194 preservice teachers studying at Beijing Normal University (BNU) and 149 in-service teachers who enrolled in a master program at BNU participated in the study. The Smart Classroom Inventory (SCI) a ten-component inventory revised from the previous study, was used to collect the data. Independent-samples t-tests and paired-samples t-tests revealed that: (a) both preservice teachers and in-service teachers reported significantly lower experiences of TRCs than their expectations of ideal ones in terms of most dimensions, with the only exception that preservice teachers’ Technology usage. (b) Whether in existing TRCs, or in ideal ones, both preservice teachers and in-service teachers reported relative lower scores of Flexibility, Learning data, Differentiation, Investigation, and Cooperation than other dimensions. (c) Preservice teachers reported significantly higher scores of Flexibility, Technology usage, Learning data, Differentiation, Investigation, and Cooperation than in-service teachers, while in-service teachers reported significantly higher scores of Physical design, Student Cohesiveness, Equity, and Learning experiences than preservice teachers.4) Preservice teachers reported significantly higher expectation of ideal Physical design, Differentiation than in-service teachers, while they reported significantly lower expectations of ideal Flexibility, Student Cohesiveness, Equity, and Learning experience than in-service teachers. Implications for preservice teachers’ education and in-service teachers’ professional development were discussed.